Analyzing ESG's Role as a Mediator in Corporate Resource Allocation and Financial Outcome - Senjani, Yayu Putri; Putra, Rosyid Nur Anggara (Akuntabilitas, 2024)
Sustainable finance is a key focus for the Financial Services Authority (OJK) to support a green economy, yet the financial sector's understanding of its role remains limited. This study examines data from 12 companies listed on the SRI KEHATI Index over a 10-year period (2011-2020), analyzing the impact of corporate resource allocation on ESG performance and financial outcomes. The results show that investments in research and development (R&D) and cash flows directed toward investment activities significantly enhance financial performance, while human resource expenditures have no discernible effect. These findings align with the resource-based view, suggesting that innovation and strategic investments are more effective in improving profitability than labor-related costs. Moreover, ESG performance does not mediate the relationship between company resources and profitability, indicating that, for the companies studied, ESG factors have yet to be a significant driver of financial performance, reflecting the financial industry's limited integration of sustainable finance.